Performance analysis of cross-country skiing by using automated identification of subtechniques - Ishige, Y.; Fujita, Z.; Sakurai, Y. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
In cross-country skiing, skiers use several different skiing techniques. When skiers compete, they choose the optimal subtechnique for themselves according to the gradient of the terrain in order to maintain a high velocity. A number of recent cross-country skiing studies have reported the relationship between performance in cross-country skiing and the characteristics of each subtechnique by employing a global navigation satellite system (GNSS), video camera, and mobile sensors(Andersson et al., 2010; Marsland et al., 2012). The aim of the current study was to evaluate the skier`s performance by using automated identification of subtechniques.